Within-plate Volcanism in upper Triassic to lower Jurassic Pucara Group carbonates (Central Peru) - Rosas, Silvia (1996)
The Pucará Group platform carbonates (Upper Triassic - Lower Jurassic) were laid down in northern and central Peru in a NNW-SSE elongated basin (Fig. 1). They represent the first sediments of the Andean cycle, the beginning of which is marked by a Norian transgression (Mégard, 1978). The sedimentary evolution of the Pucará Group can be explained in terms of a large transgressive/regressive second order sequence which consists of predominantly shallow water carbonates including a maximum flooding period represented by ammonite-bearing bituminous calcareous shales. Detailed investigations in the southern part of the basin show that the Pucará Group thickens progressively from west to east in the form of a half-graben (Fig. 2). This can be explained by asymmetrical subsidence during sedimentation such being assisted by contemporaneous faulting along the eastern margin of the basin (permitting rapid subsidence) and a stable hinge zone to the west. Synsedi - mentary tectonics at the eastern edge led to the formation of discrete structural blocks with extreme variations in thickness and facies. It has been suggested that, during burial diagenesis, these faults served as channelways for the basinal brines responsible for MVT-mineralization (Fontboté et al., 1995, Spangenberg, 1995, and Moritz et al., 1996).